PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN KEMAMPUAN MENGANALISIS UNSUR INSTRINSIK CERITA LEGENDA SISWA KELAS V SDN 034 SUKAJADI KOTA PEKANBARU - Otang Kurniaman; Eddy Noviana; Misliati Misliati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2013)
This reseach based on the result of ability to analize element of legend story of fifth grade studentsSDN 034 Sukajadi at second semester 2010/2011. From 30 students it was just 40% students achievedclassical completeness meanwhile it should be 80% students achieved within minimum completenesscriterion set in the school was 65,00. The formulated problem in this reseach wether applicationcooperative learning model tipe Numbered Heads Together (NHT) can improve ability to analizeelement of legend story of fifth grade students SDN 034 Sukajadi Pekanbaru? The aim of this reseachis to improve ability to analize element of legend story with application of cooperative learning modeltipe Numbered Heads Together (NHT). This reseach used classroom action research throughcooperative learning model tipe Numbered Heads Together (NHT) at fifth grade students SDN 034Sukajadi Pekanbaru within 30 students. This action was done at May 2011. The initial result of abilityto analize element of legend story was 60 with 40% or 12 students got scores above 65 or minimumcompleteness. After application of cooperative learning model tipe Numbered Heads Together (NHT)in UH I of cycle I, It was obtained the average score of students’ ability to analize element of legendstory around 68,33 within 60% or 18 students completeness. In UH II of cycle II the average score ofstudents’ ability increased into 78, within 89,91% or 27 students completeness. So that the hypothesesof this reseach “application cooperative learning model tipe Numbered Heads Together (NHT) canimprove ability to analize element of legend story of fifth grade students SDN 034 Sukajadi PekanbaruSukajadi Pekanbaru”, was acceptan.Keyword: Cooperative, Legend